1996
DOI: 10.1111/j.1476-5381.1996.tb15594.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation by 5‐HT3 receptors of an excitatory effect of 5‐HT on dorsal vagal preganglionic neurones in anaesthetized rats: an ionophoretic study

Abstract: 1 Extracellular recordings were made from 141 vagal preganglionic neurones in the dorsal vagal nucleus (DVN). The effects of ionophoretic administration of 5-hydroxytryptamine (5-HT), the 5-HT3 receptor agonist, phenylbiguanide (PBG) and the antagonists, granisetron and tropisetron on these vagal preganglionic neurones were studied in pentobarbitone sodium anaesthetized rats. 2 Ionophoretic application of 5-HT at low currents (< 10 nA) increased the activity in 46 (73%) of 63 neurones tested. Application of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
(54 reference statements)
6
26
0
Order By: Relevance
“…This corresponds to recent evi-(c) At a higher dence suggesting a high level of 5-HT,A receptor mRNA prese to 5-HT was sent in the dorsal motor nucleus of the vagus of the rat % reduction was (Pompeiano et al, 1994;Wright et al, 1995) and also, to in vivo work where 5-HT increases spontaneous activity of antidromically identified DVMs via a 5-HT2A 2C receptor (Wang et al, 1995a Wang et al, 1995b). However, it has not been determined whether this effect is a direct, postsynaptic one, a presynaptic action or a combination of both effects as 20 mV observed within the NTS (Glaum et al, 1992).…”
Section: -Ht 20 Tmsupporting
confidence: 81%
See 1 more Smart Citation
“…This corresponds to recent evi-(c) At a higher dence suggesting a high level of 5-HT,A receptor mRNA prese to 5-HT was sent in the dorsal motor nucleus of the vagus of the rat % reduction was (Pompeiano et al, 1994;Wright et al, 1995) and also, to in vivo work where 5-HT increases spontaneous activity of antidromically identified DVMs via a 5-HT2A 2C receptor (Wang et al, 1995a Wang et al, 1995b). However, it has not been determined whether this effect is a direct, postsynaptic one, a presynaptic action or a combination of both effects as 20 mV observed within the NTS (Glaum et al, 1992).…”
Section: -Ht 20 Tmsupporting
confidence: 81%
“…Finally, all these studies were carried out on spontaneously firing neurones; therefore little is known about the subthreshold effects of 5-HT on DVMs. This is essential if the role of 5-HT in modulating DVMs is to be defined, as in vivo studies have shown that the majority of DVMs do not spontaneously fire action potentials (Wang et al, 1995b) whereas an in vitro study stated that most DVMs were spontaneously active (Travagli et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus tractus solitarii (NTS), activation of 5-HT3 receptors blocks the chemoreflex bradycardia and inhibits both baroreflex and Bezold –Jarisch reflex responses (2427). In the dorsal vagal motor nucleus, another brainstem site that contains CVNs, activation of 5-HT3 receptors mediates excitation of CVNs (28, 29). Furthermore, 5-HT3 receptors are involved in physiological responses to hypoxia in the peripheral nerve system.…”
mentioning
confidence: 99%
“…In the remaining experiments, guinea pigs sensitized to ovalbumin (OA) were submitted to an antigenic challenge with 400 μg/kg OA i.v., a dose that in this animal model usually produces an acute maximal bronchoconstriction in 2-6 min, with a gradual return to basal values in ∼15-30 min. To determine the functional role of 5-HT in the allergic bronchoconstriction, sensitized guinea pigs received a combination of 300 μg/kg methiothepin (antagonist of 5-HT 1 , 5-HT 2 , 5-HT 5 , 5-HT 6 , and 5-HT 7 receptors) [13,14] plus 3 mg/kg tropisetron (antagonist of 5-HT 3 and 5-HT 4 receptors) [15][16][17], both admin-istered by the i.v. route approximately 10 min before the antigenic challenge.…”
Section: Methodsmentioning
confidence: 99%